PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL INTERAKTIF BERBASIS CANVA UNTUK MATERI POLA BILANGAN DI KELAS IV - Patra Aghtiar Rakhman; Reksa Adya Pribadi; Puspita Sulistya Maharani; Andhita Mujiyati; Rusbia Inayah (Jurnal Ilmiah Matematika Realistik, 2026)
This study aims to develop and evaluate the feasibility of an interactive digital learning medium based on Canva for number patterns for fourth-grade elementary school students. This study was conducted using the Research and Development method with the ADDIE development model, which includes the analysis, design, development, implementation, and evaluation stages. The analysis stage was conducted to identify the needs of teachers and students through observation and interviews, which revealed a lack of engaging and relevant teaching materials. In the design and development stages, the media was created by integrating text, illustrations, audio, and interactive features via the Canva platform to facilitate understanding of number pattern concepts. The product was then validated by subject matter experts and media experts, resulting in an average score of 80.25%, indicating a “highly suitable” category for use. Implementation was carried out through a limited pilot test with students, yielding a positive response rate of 85%, indicating that this interactive media is capable of enhancing student learning. This final evaluation demonstrates that the Canva-based interactive media is easily accessible, visually appealing, and facilitates understanding of number pattern material; its user-friendly navigation makes it suitable for use in learning settings anywhere. This differs from previous research, which focused solely on using it as a presentation or visualization tool. Based on these overall findings, the Canva-based digital learning media is deemed suitable and effective for implementation as an alternative for learning in mathematics education.